Pengaruh Ulasan Konsumen pada Media Sosial Twitter Terhadap Keputusan Pembelian di Shopee - Fatih Adiyatma, Muhammad; Trianasari, Nurvita (Rifa'Institute, 2022)
The development of the digital era in Indonesia has caused the internet to become a necessity for the Indonesian people. This makes Indonesia one of the largest online markets in Southeast Asia, with e-commerce as the main industry driver. Behind this high development, consumer behavior can be an important component in understanding business trends or business opportunities for business owners on e-commerce platforms. In addition, the dissemination of information on microblog services can be quickly spread, and this information can be easily searched by typing keywords or keywords from the information to be searched. In addition, the number of Twitter users in Indonesia has been at the top of the microblogging social media platform category in recent years. The purpose of this study is to explain how the influence of consumer reviews on Twitter social media on purchasing decisions at Shopee partially and simultaneously. The findings in this study were obtained using a quantitative method with a deductive type of research by distributing questionnaires to 385 respondents. Data processing using IBM SPSS Statistics software version 25, ranging from validity and reliability tests to data analysis techniques using multiple linear regression analysis techniques. The results of this study provide a quantitative description and show that behavioral perceptions, subjective norms, peer communication, emotional support, and parasocial interactions each have a positive and significant effect on purchasing decisions at Shopee Indonesia